Modeling movement patterns to identify thresholds of functional connectivity in fragmented forest landscapes - Peterson, Michaela C.; Bradham, Jennifer; Ferraro, Kristy; Guillet, Max; Keuroghlian, Alexine; Ribeiro, Milton [UNESP]; Jorge, Maria Luisa S.P. (Elsevier, 2025)
Deforestation and fragmentation are rapidly altering forest ecosystems worldwide. While several studies have identified thresholds at which forest loss and fragmentation lead to species loss, few have explored thresholds at which ecological processes break down prior to biodiversity loss. Here, we present an agent-based model designed to examine the impact of habitat loss and fragmentation on the landscape-use patterns of highly mobile mammals in forest ecosystems. While our model can be easily adapted to a range of species, we provide a case study to identify essential thresholds of forest loss using movement data from the white-lipped peccary (Tayassu pecari), a wide-ranging, keystone species in Neotropical forests. We found that at least 40 % forest cover was required to preserve functional landscape connectivity, and at least 60 % forest cover was required to preserve the movement patterns displayed by this species in fully forested landscapes. We also found that increasing habitat fragmentation exacerbated the effects of forest loss. Our results provide further evidence that key thresholds of forest cover exist for preserving ecological processes and biodiversity in Neotropical forests.